2010
DOI: 10.1590/s0104-07072010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologia móvel à beira do leito: processo de enfermagem informatizado em terapia intensiva a partir da cipe 1.0®

Abstract: RESUMO:Produção tecnológica e estudo metodológico baseado na evidência que avaliou com os enfermeiros de Terapia Intensiva os critérios de Ergonomia e Usabilidade do Processo de Enfermagem Informatizado desenvolvido em um dispositivo tecnológico móvel a partir da Classificação Internacional para as Práticas RESUMEN:Producción tecnológica e investigación metodológica basada en la evidencia que tuvo por objeto evaluar, con los enfermeros de las Unidades de Cuidados Intensivos, los criterios de Ergonomía y Usabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 23 publications
0
22
0
13
Order By: Relevance
“…It is obvious that these innovations must be assessed in terms of their impact on professional practice and patient safety. 20 One study made a metaphorical comparison between the historical phases of technology construction in nursing and the cyclic phases of the moon, considering the current time as a 'full moon, marked by the presence of records, patents in the National Institute of Industrial Propriety (Instituto Nacional de Propriedade Industrial -INPI), and the development of research proposals involving the production of nursing technologies, supported by funding agencies, in addition to theses and publications with growing visibility. However, the author questions if the use of information technology is resulting in more time to generate new sensitivities in nursing care, promoting the explicitation of the art underlying the practice.…”
Section: Innovation Technology and Implications For The Health Sectormentioning
confidence: 99%
“…It is obvious that these innovations must be assessed in terms of their impact on professional practice and patient safety. 20 One study made a metaphorical comparison between the historical phases of technology construction in nursing and the cyclic phases of the moon, considering the current time as a 'full moon, marked by the presence of records, patents in the National Institute of Industrial Propriety (Instituto Nacional de Propriedade Industrial -INPI), and the development of research proposals involving the production of nursing technologies, supported by funding agencies, in addition to theses and publications with growing visibility. However, the author questions if the use of information technology is resulting in more time to generate new sensitivities in nursing care, promoting the explicitation of the art underlying the practice.…”
Section: Innovation Technology and Implications For The Health Sectormentioning
confidence: 99%
“…6,22,[28][29][30][31][32] The first study developed and evaluated a proposal for clinical evaluation and nursing diagnoses and interventions for the cardiovascular system, using ICNP® version β1. 28 The second study proposed and evaluated the development of NP stages for the respiratory system, also applying ICNP® version β1.…”
Section: Application Of the Icnp® Classification System In Nursing CLmentioning
confidence: 99%
“…It was concluded that this computerized system using a PDA interface was a coherent, effective, possible and consistent proposal because, in addition to permitting the integration between research, professional practice and teaching, it allowed nurses to provide bedside care to patients. [31][32] These studies also pointed out that the ICNP® permitted nurses to organize and develop their logical rationale in the process of taking care of ICU inpatients, because it permitted these professionals to establish a concrete relationship between the clinical evaluations and the nursing diagnoses, interventions and outcomes through the use of computerized tools. 6,22,[28][29][30][31][32] In this sense, it is highlighted that the computerized NP applying the ICNP® can contribute to nursing, as it promotes the improvement of healthcare quality, stimulates reflexive and affective thinking, facilitates planning, decision making, communication, and management, and promotes changes to the organizational structure.…”
Section: Application Of the Icnp® Classification System In Nursing CLmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] One of the major challenges to be overcome by nursing is the effective and qualified implementation of the clinical record, making it more complete, detailed and integrated with the records/information sharing systems of other health care professionals. 1,4,[17][18][19][20][21][22] The nurses must ensure that their need for information and knowledge is met. This huge task, allied with the need to guarantee the continuity of nursing care, and consequently the patient's safety, can be achieved through the integration of information and computing systems, by means of the resources made available by the ICTs.…”
Section: Health Information and Computing Systems: The Electronic Recmentioning
confidence: 99%